Addition of Tocilizumab to the Standard of Care Reduces Mortality in Severe COVID-19: A Systematic Review and Meta-Analysis - Boregowda, Umesha; Perisetti, Abhilash; Nanjappa, Arpitha; Gajendran, Mahesh; Kutti Sridharan, Gurusaravanan; Goyal, Hemant (Frontiers in Medicine, 2020)
Introduction: Tocilizumab is an anti-interleukin-6 antibody that has been used for the treatment of severe coronavirus disease 2019 (COVID-19). However, the concrete evidence of its benefit in reducing the mortality in severe COVID-19 is lacking. Therefore, we performed a systematic review and meta-analysis of relevant studies that compared the efficacy of Tocilizumab in severe COVID-19 vs. standard of care alone. Methods: Literature search for studies that compared ‘Tocilizumab’ and ‘Standard of care’ in the treatment of COVID-19 was done using major online databases from December 2019 to June 14th, 2020. Search words ‘Tocilizumab,’ ‘anti-interleukin-6 antibody,’ and ‘COVID-19’ or ‘coronavirus 2019’ in various combinations were used. Articles in the form of abstracts, letters without original data, case reports, and reviews were excluded. Data was gathered on an excel sheet, and statistical analysis was performed using Review Manager 5.3. Results: Five studies were eligible from 693 initial studies, including 3,641 patients (64% males). There were thirteen retrospective studies and three prospective studies. There were 2,488 patients in the standard of care group (61.7%) and 1,153 patients (68.7%) in the Tocilizumab group. The death rate in the tocilizumab group, 22.4% (258/1153), was lower than the standard of care group, 26.21% (652/2,488) (Pooled odds ratio 0.57 [95% CI 0.36-0.92] p=0.02). There was a significant heterogeneity (Inconsistency index= 80%) among the included studies. Conclusion: The addition of Tocilizumab to the standard of care might reduce the mortality in severe COVID-19. Larger randomized clinical trials are needed to validate these findings.